Introduction of an automated service for the laboratory confirmation of meningococcal disease in Scotland. Issue 7 (1st July 2001) - Clarke, S C; Diggle, M A; Reid, J A; Thom, L; Edwards, G F S
Abstract : The Scottish Meningococcus and Pneumococcus Reference Laboratory provides a national service for the laboratory confirmation of meningococcal and pneumococcal disease in Scotland. The main tests used for the laboratory confirmation of meningococcal disease are culture, the polymerase chain reaction (PCR), antibody testing, and more recently DNA sequencing. This paper describes the automation of PCR for the laboratory confirmation of meningococcal disease and the typing of meningococcal isolates using DNA sequencing. Both methods have been automated using a robotic liquid handler and automated DNA sequencer. These methods, along with standard culture phenotyping and antibody testing, provide Scotland with an excellent service for the confirmation of meningococcal disease.